Sexuality, sexual and reproductive health: an exploration of the knowledge, attitudes and beliefs of the Greek-Cypriot adolescents - Kouta, Christiana; Tolma, Eleni L. (My University, 2008)
This study examines the knowledge, attitudes and beliefs of Greek-Cypriot adolescents regarding sexuality, sexual and reproductive health in Cyprus. This is the first study in Cyprus that focuses on these issues. During the study, a survey was administered to a random sample of third grade students (N = 697, Mean age = 14 ± 1 years, 48% males). Descriptive and comparative statistics were primarily used for the data analysis. The results indicated that young Greek-Cypriots have limited knowledge on sexual health issues and that there are gender differences regarding role expectations of sexuality. Thus, in the promotion of healthy sexuality and sexual behaviours among youth, practitioners should include gender and cultural perspectives. Qualitative research is needed to explore in depth how young Greek-Cypriots feel about sexuality and sexual and reproductive health.
Keywords: Reproductive health--Cyprus; Reproductive health--Greece; Adolescents; Sexuality; Gender